Development and validation of a sensitive enzyme-linked immunosorbent assay for clonidine hydrochloride in pig urine and pork samples. Issue 1 (1st January 2021) - Wang, Yao; Cao, Jinbo; Sun, Yaning; Xing, Yunrui; Pang, Xinghao; Chen, Xiujin; Fei, Peng; Li, Zhaozhou; Cheng, Qiaofen; Kang, Huaibin; Hu, Xiaofei
ABSTRACT: Clonidine hydrochloride (CLO) is a new substitute for a traditionally used adrenergic agonist. The illegal use of CLO in the livestock industry possess potential harm to human health. Hence, it is an urgent need for the rapid detection of CLO residues. Here, we prepared a highly sensitive and specific monoclonal antibody (mAb) and it used to develop an indirect competitive ELISA (ic-ELISA) for the rapid screening of CLO residues. The limit of detection and limit of quantification values of ic-ELISA were as follows: 0.033 and 0.054 ng/mL for pig urine and 0.061 and 0.096 ng/mL for pork, respectively. Recovery experiment indicated that the ic-ELISA posed outstanding accuracy and precision. Furthermore, the results of ic-ELISA were strongly correlated to the results of HPLC. Thus, the ic-ELISA provided a sensitive and rapid on-site detection of CLO residues in pig urine and pork samples.